2019
DOI: 10.1016/j.compgeo.2018.09.019
|View full text |Cite
|
Sign up to set email alerts
|

On a fabric evolution law incorporating the effects of b-value

Abstract: In this paper, the effects of the intermediate stress ratio, i.e., b-value (b=(2-3)/ (1-3)), on the contact normal-based fabric evolution of granular material, are incorporated into an extant hybrid fabric evolution law. The new evolution law is validated by Discrete Element Method (DEM) simulation results under monotonic shearing with different b-values. Predictions of the proposed generalized fabric evolution law agree well with the DEM simulation results. This evolution law can be widely used for constituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…In most cases of three-dimensional materials, the frequency distribution of contact normals in a granular assembly can be expressed by a spherical harmonic series with the second-order approximation [21,93] where n denotes the unit contact normal at a contact. According to Kanatani [23], the tensor F in Eq.…”
Section: Definition Of Fabric Tensormentioning
confidence: 99%
See 4 more Smart Citations
“…In most cases of three-dimensional materials, the frequency distribution of contact normals in a granular assembly can be expressed by a spherical harmonic series with the second-order approximation [21,93] where n denotes the unit contact normal at a contact. According to Kanatani [23], the tensor F in Eq.…”
Section: Definition Of Fabric Tensormentioning
confidence: 99%
“…1. In a general stress space, it is found that both M and M F are dependent on the b value [93]. For simplicity, we first take M and M F as constants here, and their dependency on the b value will be discussed in Sect.…”
Section: Description Of the Anisotropic Critical Statementioning
confidence: 99%
See 3 more Smart Citations